2018
DOI: 10.1007/s13197-018-3281-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bambara groundnut supplementation on the physicochemical properties of rice flour and crackers

Abstract: This study evaluated the effect of bambara groundnut supplementation on the physicochemical properties of local rice flour and baked crackers. Bulk and true density, porosity, water absorption index, oil absorption capacity, pasting properties by RVA, morphological appearance by SEM, color by calorimetry, and textural properties by TA.XT2 analysis of wheat and two formulations of rice-legume flours and crackers were studied. Moisture (10.94%) and carbohydrate (77.42%) levels were significantly greater in wheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…These findings were consistent with the results of physical properties that riceberry incorporating cracker exhibited the least expansion and decreased hardness. This result is due to an essential structure-building protein of gluten in wheat flour which can help entrap gas in the dough resulting in larger gas bubbles, but lacked in rice flour (Nammakuna et al 2015;Yeboah-Awudzi et al 2018). This observation is similar with Jiamjariyatam (2019) who observed that the morphology of puffed crackers was more compact and with more homogenous air cell walls when the RB percentage was increased.…”
Section: Microstructure Of Crackersupporting
confidence: 74%
See 1 more Smart Citation
“…These findings were consistent with the results of physical properties that riceberry incorporating cracker exhibited the least expansion and decreased hardness. This result is due to an essential structure-building protein of gluten in wheat flour which can help entrap gas in the dough resulting in larger gas bubbles, but lacked in rice flour (Nammakuna et al 2015;Yeboah-Awudzi et al 2018). This observation is similar with Jiamjariyatam (2019) who observed that the morphology of puffed crackers was more compact and with more homogenous air cell walls when the RB percentage was increased.…”
Section: Microstructure Of Crackersupporting
confidence: 74%
“…According to the texture of the cracker incorporated with RB, it was crumbly, brittle, and had low expansion. This was due to rice flour lacking gluten which is the most important protein contributing to water retention, formation of elastic structures that entrap air and expansion of dough and the end products (Sivaramakrishnan et al 2004;Nammakuna et al 2009;Yeboah-Awudzi et al 2018). Even the addition of milk protein from cheese to replace the gluten did not have an effect on improving texture in RB-based cracker.…”
Section: Physical Properties Of Crackermentioning
confidence: 99%
“…They are potential foods for fortification programs targeting school children and adult alike. Studies on the inclusion of Bambara groundnut flour in these products showed variable results in terms of their physical and functional properties (83)(84)(85). These variations could be due to different formulations and production methods used, which might also explain the differences in nutritional and sensory qualities among these products.…”
Section: Snacks: Crackers/biscuits/extruded Productsmentioning
confidence: 99%
“…The L value result suggests that the masa flour without Bambara was whiter in appearance, which could be attributed to variation in the composition of the grains. Enriched masa flour samples showed a significant decline in all the colour values (L, a and b) with an increase in the storage period (Table 1), which could be due to the Maillard reaction in the stored flour (Ward et al, 1998;Yeboah-Awudzi et al, 2018). This seems plausible since the presence of protein from Bambara grains and carbohydrate in the masa flour may facilitate the Maillard reaction.…”
Section: Resultsmentioning
confidence: 96%